Visceral Leishmaniasis in the Muzaffapur Demographic Surveillance Site: A Spatiotemporal Analysis - Hasker, Epco (Am J Trop Med Hyg, 2018)
In the Indian subcontinent, visceral leishmaniasis (VL) has a strongly clustered distribution. The “index case approach” is promoted both for active case finding and indoor residual spraying (IRS). Uncertainty exists about the optimal radius. Buffer zones of 50–75 m around incident cases have been suggested for active case finding, for IRS the recommendation is to cover a radius of 500 m. Our aim was to establish optimal target areas both for IRS and for (re)active case finding. We plotted incident VL cases on a map per 6-month period (January–June or July–December) and drew buffers of 0 (same household), 50, 75, 100, 200, 300, 400, and 500 m around these cases. We then recorded total population and numbers of VL cases diagnosed over the next 6-month period in each of these buffers and beyond. We calculated incidence rate ratios (IRRs) using the population at more than 500 m from any case as reference category. There was a very strong degree of spatial clustering of VL with IRRs ranging from 45.2 (23.8–85.6) for those living in the same households to 14.6 (10.1–21.2) for those living within 75 m of a case diagnosed, during the previous period. Up to 500 m the IRR was still five times higher than that of the reference category. Our findings corroborate the rationale of screening not just household contacts but also those living within a perimeter of 50–75 m from an index case. For IRS, covering a perimeter of 500 m, appears to be a rational choice.